Prevalence of Appendical Metastasis in Primary Surgery of Ovarian Epithelial Cancer: Prevalensi Metastasis Apendiks Pada Bedah Primer Kanker Epitel Ovarium - Laila Nuranna; Jan H. Amili; Sigit Purbadi; Nessyah Fatahan (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To determine the prevalence of metastasis to appendix from primary surgery of ovarian epithelial cancer at National General Hospital Dr. Cipto Mangunkusumo (RSCM), Indonesia.Methods: A cross sectional study was done using ovarian epithelial cancer patient medical record whose primary ovarian cancer and appendectomy surgery were conducted on July to December 2019 at RSCM. Patients without appendix histopatology result and previous chemotherapy were excluded in this study. Consecutive method and random sampling were used in this study.Results: : A total of 80 subjects were included in this study. Subjects have average age of 48 years old. Out of all samples, 43 samples (53.8%) were defined as stage I patient, 7 subjects (8.8%) as stage II, 30 subjects (37.5%) as stage III, and none as stage IV. Appendectomy were done and eight subjects (10%) experienced metastasis to appendix. A total of 19 subjects (23.8%) had chronic appendicitis and 53 subjects (66.3%) did not have metastasis to the appendix. Among eight subjects having appendix involvement, 4 had mucinous histology, 2 serous, and 2 endometrioid. Six out of eight were diagnosed at clinical stage III and two were diagnosed at stage I.Conclusion: The prevalence of appendix metastases from primary surgery in ovarian epithelial cancer at RSCM was 10%. Based on this research, appendectomy can be considered on ovarian cancer surgeryKeywords: appendix, metastasis, ovarian cancer. Abstrak Tujuan: Mengetahui prevalensi metastasis kanker epitelial ovarium ke apendiks pada pembedahan primer kanker epitelial ovarium di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo (RSCM), Indonesia. Metode: Penelitian ini merupakan studi potong lintang menggunakan data rekam medis pasien kanker ovarium epitelial yang menjalani pembedahan primer dan apendiktomi pada bulan Juli hingga Desember 2019 di RSCM Pasien tanpa histopatologi apendiks atau pernah dilakukan kemoterapi sebelumnya dieksklusi dari penelitian. Digunakan metode pengambilan sampel secara acak. Hasil: Didapatkan 80 subjek penelitian yang diikutsertakan dalam penelitian. Dari 80 subjek penelitian, didapatkan rerata usia 48 tahun. Sebanyak 43 subjek (53,8%) didiagnosis dengan stadium I, 7 subjek (8,8%) sebagai stadium II, 30 subjek (37,5%) stadium III. Dari 80 subjek yang menjalani apendiktomi, didapatkan 8 subjek (10%) anak sebar ke apendiks, 19 subjek (23,8 %) apendisitis kronis, 53 subjek (66,3%) tidak terdapat anak sebar. Dari 8 subjek yang terdapat anak sebar ke apendiks dengan temuan histologi 4 musinosum, 2 serosum, 2 endometroid. Sebanyak enam dari delapan subjek terdiagnosis pada stadium klinis stadium III dan dua lainnya pada stadium klinis satu. Kesimpulan: Prevalensi metastasis apendiks pada operasi primer kanker ovarium epitelial di RSCM adalah sebesar 10%. Berdasarkan hasil penelitian ini, apendektomi dapat dipertimbangkan dilakukan pada pembedahan baik stadium awal maupun stadium lanjut.Kata kunci: , apendiks , kanker ovarium, metastatis